Thermodynamic modelling as a basis for forecasting phase states of hydrocarbon fluids at great and super-great depths - Oleg M. Prishchepa; Denis S. Lutskii; Sergei B. Kireev; Nikita V. Sinitsa (Записки Горного института)
The possibility of discovering oil and gas occurrences at great (more than 5 km) and super-great (more than 6 km) depths is considered in two aspects. The first one is the preservation conditions of large hydrocarbon accumulations forming at depths to 4 km and caused by different geological and tectonic processes occurring at great and super-great depths with partial oil-to-gas transformation. It was ascertained that among the factors controlling preservation of liquid and gaseous hydrocarbons are the temperature, pressure, subsidence rate (rate of temperature and pressure increase), time spent under ultrahigh thermobaric conditions, and initial composition of organic matter. The possibility of existence of liquid components of oil at great and super-great depths is characteristic of sedimentary basins of China, the Gulf of Mexico, the Santos and Campos basins on the Brazilian shelf, and in the Russian Federation it is most probable for the Caspian Depression, some submontane troughs and zones of intense accumulation of young sediments. Determination of critical temperatures and pressures of phase transitions and the onset of cracking is possible using the approach considered in the article, based on estimation of organic matter transformation degree, kinetic and thermobaric models taking into account the composition of hydrocarbon fluid. The second aspect is the estimation of composition of hydrocarbons associated with rocks forming at great depths or rocks transformed under conditions of critical temperatures and pressures. This aspect of considerable science intensity can hardly be considered as practically significant. The study focuses on the investigation of the possibilities of thermodynamic modelling and the use of alternative methods for studying the transformation degree of liquid formation fluid into components of the associated gas through the example of two areas with identified oil, condensate and gas accumulations.